INCREASED SECURITY Through Open Source. - Hoepman, Jaap-Henk; Jacobs, Bart (Communications of the ACM, 2007)
The article focuses on the security issues surrounding open source software. It is suggested that there is a well-established conviction within the computer security community that publishing designs and protocols contribute to the security of systems built on them. The article addresses whether programmers should publish source code in addition to the designs and protocols. The impact of open source on security and transparency of a software system is discussed. The article concludes that openness of the source will increase its security.